2015
DOI: 10.1038/ni.3096
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis suppresses innate immunity by coopting the host ubiquitin system

Abstract: Mycobacterium tuberculosis PtpA, a secreted tyrosine phosphatase essential for tuberculosis pathogenicity, could be an ideal target for a drug against tuberculosis, but its active-site inhibitors lack selectivity over human phosphatases. Here we found that PtpA suppressed innate immunity dependent on pathways of the kinases Jnk and p38 and the transcription factor NF-κB by exploiting host ubiquitin. Binding of PtpA to ubiquitin via a region with no homology to human proteins activated it to dephosphorylate pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
165
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(184 citation statements)
references
References 41 publications
7
165
2
Order By: Relevance
“…156 Our data showed that Mtb PtpA is activated to directly dephosphorylate p-JNK and p-p38 by binding to the host ubiquitin via a brand new UIM-like region, resulting in the repression of innate immunity. 157 Furthermore, we observed that PtpA interferes with the association between TAB3 and K63-linked ubiquitin chains by competitively interacting with the NZF domain of TAB3, thus subverting NF-κB activation. Our discovery that Mtb commandeers the ubiquitin system provides novel insight into the Mtb-macrophage interaction and reveals potential pathogen-host interface-based targets for the treatment of tuberculosis.…”
Section: Mycobacterium Tuberculosismentioning
confidence: 93%
“…156 Our data showed that Mtb PtpA is activated to directly dephosphorylate p-JNK and p-p38 by binding to the host ubiquitin via a brand new UIM-like region, resulting in the repression of innate immunity. 157 Furthermore, we observed that PtpA interferes with the association between TAB3 and K63-linked ubiquitin chains by competitively interacting with the NZF domain of TAB3, thus subverting NF-κB activation. Our discovery that Mtb commandeers the ubiquitin system provides novel insight into the Mtb-macrophage interaction and reveals potential pathogen-host interface-based targets for the treatment of tuberculosis.…”
Section: Mycobacterium Tuberculosismentioning
confidence: 93%
“…PtpA blocks the fusion between phagosome and lysosome, and inhibits phagosome acidification by binding to the subunit H of H þ -ATPase and dephosphorylating human class C Vacuolar Protein Sorting VPS33B in homotypic vacuole fusion and vacuole protein sorting complex (HOPS) [10,11]. PtpA was shown to inhibit innate immune response through dephosphorylation of Jnk and p38 [28]. PtpA also represses host apoptosis by dephosphorylating GSK3a (Glycogen Synthase Kinase 3a) [29] and potentially macrophage's bioenergetics state [30].…”
Section: Introductionmentioning
confidence: 98%
“…Upon DNA virus infection, TRIM11 binds to absent in melanoma 2 (AIM2) via its PS domain and mediates AIM2 degradation via selective autophagy . Recent reports have demonstrated that Mtb tyrosine phosphatase suppresses the activation of activator protein‐1 and NF‐κB in macrophages by co‐opting the host ubiquitin system . These observations suggest a potential role of TRIM in Mtb infection.…”
Section: Introductionmentioning
confidence: 99%